EMOTIVES OF SURPRISE IN MODERN ENGLISH POETRY - Khvostenko, Y.; Redka, I. (Studia Philologica, 2021)
The paper focuses on linguistic manifestation of emotion of surprise in modern English poetic texts. The study is guided by the statement that emotions – psychosomatic processes – can be fixed in fictional texts (including the poetic ones) in the form of emotives – the linguistic units that manifest emotions and/or feelings of the addresser. The emotion of surprise differs from other basic emotions of a person due to its ambivalence and specific prerequisites to emergence. As surprise comes forth unexpectedly, the study looks for basic situations in the context of poetic texts when emotives of surprise appear. To study the phenomenon, the concept of emotional situation is employed. It marks the circumstances under which the persona experiences the emotion of surprise. The results obtained from the analysis of modern English poems distinguish several emotional situations in which emotives of surprise appear. They occur at the junction of image-bearing spaces of 1) dream and reality; 2) reality and fantasy; 3) expectations and their fulfilment; 4) two contrasting situations in reality. These image-bearing spaces may have either contrasting or complementing features. The defeated expectancy effect that occurs due their interaction manifests itself verbally via the emotives of surprise. Key words: surprise, emotion, emotive, emotiology, emotional situation.